Building TariPedia App as A Typical Balinese Performance Encyclopedia on Mobile Device Platform - Hanif, Muhammad Hanif; Arya Kadyanan, I Gusti Agung Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 8 No 2 (2019): Jeliku Volume 8 No 2, November 2019, 2020)
Indonesia is a country with a variety of cultures and arts. Traditional art dance is one of Indonesia's arts which is one of the important aspects in supporting Indonesian culture and even tourism. Traditional dance has a special attraction to be enjoyed while staying in the midst of rapid development. Therefore, the writer makes a market application that connects the studios, dance groups, and dancers with traditional dancer tenants. TariPedia makes it easy for studio owners, service providers, and event organizers to market their services so that they can be more easily reached by the public and can increase sales of their services with the payment feature through the application. Therefore by developing TariPedia with Prototyping Method and Java Language in its development, TariPedia will continue facilitates the community, especially in the fields of traditional dance and at the same time modernizing regional arts.